Parents' views of the relevance of a violence prevention program in high, medium, and low human development contexts. (July 2017) - Durrant, Joan; Plateau, Dominique Pierre; Ateah, Christine A.; Holden, George W.; Barker, Leslie A.; Stewart-Tufescu, Ashley; Jones, Alysha D.; Ly, Gia; Ahmed, Rashid
Every day, almost one billion children around the world experience violent punishment. Eliminating all violence against children is a key target of the United Nations' 2030 Agenda for Sustainable Development. This is a monumental challenge due to the diversity of cultural, economic and social contexts in which children live. Violence-prevention programs developed in wealthy countries cannot be assumed to be transferable to low- and middle-income countries. We assessed the relevance of Positive Discipline in Everyday Parenting (PDEP) to 525 parents living in countries with high ( n = 201), medium ( n = 166), or low ( n = 158) Inequality-Adjusted Human Development Indices. The outcome measures were parents' satisfaction with the program and their perceptions of its impact on their parenting. Across IHDI categories, almost all parents were "mostly" or "very satisfied" with the overall program (98.4%), the PDEP parent book (97.9%), and the program activities (97.8%). Parent satisfaction scores were higher in the Low IHDI category than in the High IHDI category. Across IHDI categories, large majorities of parents perceived PDEP as having positive impacts on their parenting. While parents in the Medium IHDI category had the strongest perceptions of PDEP's positive impact, more than 90% of parents in the Low IHDI category believed that the program will help them to understand their children's development and feelings, communicate better with their children, control their anger, and build stronger relationships with their children. PDEP is a promising tool for preventing punitive violence against children across human development contexts.